2016
DOI: 10.1186/s12906-016-1480-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Ayurved Siriraj Wattana recipe on functional and phenotypic characterization of cytokine-induced killer cells and dendritic cells in vitro

Abstract: BackgroundAyurved Siriraj Wattana recipe (AVS073), has been prescribed as tonic, to increase appetite, and for pain relief. It also exhibits antioxidant, anti-inflammatory, immunomodulating and anti-cancer activities. However, the immunomodulatory effects on antigen-presenting cells and effector T cells remained elusive. We thus aimed to study the effects of AVS073 on differentiation, maturation, functions and proportions of CIK cells and monocyte-derived DCs.MethodsCIK cells and monocyte-derived DCs were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In addition, our results showed that the expression of CENPL was significantly positively correlated with many markers of immune cells, among which IRF5, a marker of M1 macrophages [ 54 ], and CCR8 [ 55 ] and STAT5B [ 56 ], markers of Treg cells, have the highest correlation. Macrophages are often divided into M1 and M2 types according to their functions.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, our results showed that the expression of CENPL was significantly positively correlated with many markers of immune cells, among which IRF5, a marker of M1 macrophages [ 54 ], and CCR8 [ 55 ] and STAT5B [ 56 ], markers of Treg cells, have the highest correlation. Macrophages are often divided into M1 and M2 types according to their functions.…”
Section: Discussionmentioning
confidence: 97%
“…The indication of this drug is older people (aging in Thai traditional medicine is defined as aged 32 and over). Moreover, the WNF has been investigated by many scientific studies to explain its pharmacological activities relating to age degeneration, including antioxidation 2 , immunomodulatory 3,4 anti-neurodegenerative, 5 and anti-inflammatory properties. 6 Anti-inflammation is one effect linked to WNF's ability to ease muscle pain compared to diclofenac in OA knee patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally prescribed as an appetite stimulant and for health improvement and promotion. Moreover, it has recently been tested for its ability to control the immunomodulatory activity of natural killer and monocyte-derived dendritic cells, osteoarthritis and gastric emptying rate (GER) [12–15]. Finally, it has been shown to convey protection against ultraviolet A-induced melanogenesis through an antioxidant/redox mechanism [11].…”
Section: Introductionmentioning
confidence: 99%